2017
DOI: 10.4103/2229-516x.205813
|View full text |Cite
|
Sign up to set email alerts
|

Study of lipid peroxidation, nitric oxide end product, and trace element status in type 2 diabetes mellitus with and without complications

Abstract: Background:Oxidative stress has become a real entity in etiopathogenesis of Type 2 diabetes mellitus (DM). It may result from steady flux of free radicals and lipid peroxides in vivo. Malondialdehyde (MDA) is a stable end product of lipid peroxidation. Accumulative evidences suggest that hyperglycemia in Type 2 DM can produce major changes in nitric oxide (NO) production as well as in its action. Alteration in metabolism of trace elements is also observed in DM.Objective:To evaluate oxidative stress, status of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…An increase in plasma concentration of MDA level in T2DM patients, controlled and uncontrolled as shown in this study, clearly reflects oxidative stress in consequence of lipid peroxidation. In concordance with the present study, Mishra and Mishra [19] reported a positive correlation between MDA level and indices of glycemic control. In the present study, comparison between controlled T2DM against uncontrolled T2DM showed no significant difference in mean plasma level of MDA.…”
Section: Discussionsupporting
confidence: 93%
“…An increase in plasma concentration of MDA level in T2DM patients, controlled and uncontrolled as shown in this study, clearly reflects oxidative stress in consequence of lipid peroxidation. In concordance with the present study, Mishra and Mishra [19] reported a positive correlation between MDA level and indices of glycemic control. In the present study, comparison between controlled T2DM against uncontrolled T2DM showed no significant difference in mean plasma level of MDA.…”
Section: Discussionsupporting
confidence: 93%
“…The fact that EGF treatment significantly reduced the nitrite levels, as the main NO‐derived oxidation product at T1 is of paramount clinical relevance. Converging types of evidence indicate that nitrosilative stress is strongly associated with a myriad of diabetes‐related complications, organs' dysfunctions, and ultimately to patients outcome . Cutaneous wound repair is also dramatically influenced by NO metabolism where an exquisite fine‐tuning is required at both organismal and in the wound milieu levels for a proper healing trajectory …”
Section: Discussionmentioning
confidence: 99%
“…34 The fact that EGF treatment significantly reduced the nitrite levels, as the main NO-derived oxidation product 35 evidence indicate that nitrosilative stress is strongly associated with a myriad of diabetes-related complications, organs' dysfunctions, and ultimately to patients outcome. 36,37 Cutaneous wound repair is also dramatically influenced by NO metabolism 38 where an exquisite fine-tuning is required at both organismal and in the wound milieu levels for a proper healing trajectory. 39 AGE are a heterogeneous group of molecules that upon their interaction with the cell-bound RAGE results in generation of oxygen radicals, pro-inflammatory cytokines, and cell adhesion molecules overexpression, altogether largely involved in diabetic multiorgan complications pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…ROS, a strong oxidant, can damage cellular macromolecules such as DNA, lipids, and proteins and can also promote lipid peroxidation [52]. MDA, the end product of lipid peroxidation, can reflect the degree of lipid peroxidation, thus reflecting the extent of the damage of liver cells [53]. 8-OHdG is a widely accepted biomarker for reflecting the oxidative DNA damages [54].…”
Section: Discussionmentioning
confidence: 99%